DISGUISED INGUINAL HERNIA. (4th January 2023) - López, J; Bosch, M; Lillo, C; Barreras, J A; Caravaca, I; García, P; Arroyo, A; Lacueva, J
Abstract: Introduction: Liposarcomas are malignant neoplasms that originate in fatty mesenchymal tissue and are the most common histological subtype of soft tissue sarcomas. They account for 1% of solid tumors in adults and are located mainly in the extremities, with the retroperitoneum being the second most frequent location. Given the rarity and aggressiveness of these tumors, it is advisable to establish a multidisciplinary approach towards them in order to improve the prognosis of patients. Clinical case: Patient who was operated upon on a scheduled and outpatient basis for a left inguinal hernia. During surgery, a preperitoneal tumor was identified that was removed and revealed a high-grade dedifferentiated liposarcoma. In a second surgical act, a tumor mass of about 10 centimeters in length was found, lodged in the left pelvis and contacting sigma, which extended into the inguinal duct and scrotal pouch. Finally, compartment surgery and a left orchiectomy with end-to-end colo-sigmoid anastomosis were performed. Discussion: Routine examination of the masses contained in the hernial sacs is recommended since, despite their infrequency (<0.1%), cases of liposarcomas that have their origin in the inguinal canal have been described. Surgery for retroperitoneal sarcomas must be compartmental, which requires the inclusion of viscera close to the tumor in the resection. Complete surgical resection R0 is the only potentially curative treatment. Compartment surgery should be performed by expert surgeons in referral centers with multidisciplinary teams to improve the prognosis of these patients.